Pengaruh Pemberian Hidrogel Kunyit (Curcuma Domestica) untuk Mengurangi Striae Gravidarum Pada Ibu Nifas di Wilayah Kerja Puskesmas Jekan Raya Kota Palangka Raya - Eline Charla Sabatina Bingan (Jurnal Forum Kesehatan, 2018)
Striae Gravidarum (SG) is a line seen on the skin of a pregnant woman's abdomen due to stretching of the skin in line with the enlargement of the uterus and abdominal wall. SG can cause itching, heat in strokes and surroundings. Even though it cannot be completely removed, the condition can be minimized by skin care. In this study, herbal therapy, which is one of the complementary and alternative methods of treatment, is preferred because of its fewer complications and lower costs compared to invasive procedures such as laser therapy and cosmetic surgery. Prevention Striae Gravidarum (SG) is the same as healing wounds and scars. To analyze the effect of administration of Turmeric Hydrogel (Curcuma Domestica) to reduce Striae Gravidarum. Experimental Research with Pretest-Posttest with Control Group Design. In the design of this study there were 2 (two) groups, namely 1 (One) intervention group and 1 control group. The intervention group was given Turmeric hydrogel and the control group was given Placebo. The bivariate analysis showed that there was a statistically significant influence on the intervention group (Turmeric Hydrogel) to reduce the Striae Gravidarum line with p-value = 0.004, whereas there was no statistically significant effect to reduce SG color with p-value = 0.510. The administration of Turmeric hydrogel (Curcuma Domestica) intervention can reduce the Striae Gravidarum (SG) line, but cannot reduce the color of SG